Implications of the Articulation Gap between Geography Learners in Secondary Schools and University - Malatji, Khashane Stephen; Singh, Rachael Jesika (Alternation:Interdisciplinary Journal for the Study of the Arts and Humanities in Southern Africa (Formerly International Journal for the Study of Southern African Literature and Languages), 2018)
There is a concern in South Africa that most learners arrive at university underprepared. This is also a major concern for students who enroll for the BEd programme specialising in geography education. Due to the learners’ articulation gap, they are unable to cope with the standard that is expected of them. Hence this study investigated the level of geography learners’ prepared-ness when they arrive at university. The aim of the study was to investigate the challenges experienced by geography students in their first-year of study. The researchers used a qualitative approach grounded in phenomenology as the research design. Purposive sampling was used to select students who failed geography education in both semesters in their first-year of study, the academic year 2016. Two lecturers who teach geography in the first-year were sampled. The geography curriculum used in the secondary schools and university were also reviewed to determine the extent of alignment between the two. A the-matic approach was used to analyse the data. The results of the study revealed that geography students enter university without proper preparation, and are therefore unable to cope with their first-year of study. The study further revealed that teachers who teach geography in secondary school are not sufficiently trained to teach geography, which results in their engaging in surface learning as opposed to deep learning. The study recommends that there be collaboration between secondary schools and universities to discuss the university’s expectations with regard to learner preparedness. Moreover, geography teachers should be trained on an on-going basis in order for them to keep up with current trends in the area of geography education.
Article published in the Alternation:Interdisciplinary Journal for the Study of the Arts and Humanities in Southern Africa (Formerly International Journal for the Study of Southern African Literature and Languages).; (2018) 91 – 108
Keywords: Geography education; Teaching strategy; Deep learning; Disadvantaged schools; Geography- Study and teaching (Secondary); Geography- Study and teaching (Higher)